Determinants of economic growth in the event of sustained war: case of Sierra Leone. (2017) - Kargbo, Mohamed; Hui, An; Li, Zhuwei; Gupta, Rakesh
The growth performance for most Sub-Sahara African countries was relatively stable in the 1970s but became volatile in the 1990s due to unstable policies and civil unrest. These scenarios were the case for Sierra Leone, the country's growth performance of the 1970s spanning to the 1990s was mixed. Given the welfare implication of economic growth, we investigate key determinants to growth in the event of sustained war in Sierra Leone from 1970 to 2010, using the error correction model (ECM). This study reveals that tertiary education, enrolment rate, population growth rate, employment rate and openness to international trade have positive correlation on growth. High budget deficit, high inflation, exchange rate instability and the civil war that erupted in the country are contributing factors for the economy's poor growth performance. This understanding is important for academics and policy makers in shaping the future economic growth.